Beyond the Illusion of Knowledge: Overconfidence and Misconceptions in Science Teachers’ Environmental Literacy and Their Impact on Behavior - Garrido Álvarez-Coto, Guiomar; Arribas-Tiemblo, Irene M.; Morcillo de Amuedo, Fernando; Arana-Cuenca, Ainhoa (American Behavioral Scientist, 2026)
Environmental literacy is essential for understanding and effectively teaching the climate system. However, discrepancies between actual and self-perceived environmental literacy can influence science-based decision-making and pro-environmental behavior. This study examines the extent of this gap among secondary science teachers and its implications for environmental education. A survey was conducted with 433 secondary science teachers, assessing actual environmental literacy through a standardized test and self-perceived literacy via a Likert-scale questionnaire. Participants’ proenvironmental behaviors were also analyzed to determine the influence of perceived and actual knowledge on their actions. Findings reveal a significant gap between actual and self-perceived environmental literacy. No direct relationship was found between beliefs about the environmental future and pro-environmental behavior. In contrast, while self-perceived literacy strongly predicts pro-environmental behavior (p < .01), actual literacy does not show a significant correlation, suggesting that individuals may act on confidence rather than scientific understanding, thereby increasing susceptibility to misconceptions and misinformation. These results underscore the urgent need for specialized earth system science training for science teachers to bridge misconceptions, enhance critical thinking, and equip educators with the necessary tools to teach climate-related topics accurately. A holistic approach to environmental education that integrates scientific knowledge, values, and action is crucial for fostering evidence-based reasoning and empowering future generations to make informed environmental decisions in the face of global challenges.
Keywords: environmental literacy; climate misconceptions; environmental beliefs; pro-environmental behavior; earth system science education